Women and scientist: the yellow light on the ivory tower - Riniardi, Zarra Zettina Wiji; Setiawati, Trias (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2021)
The study purposes were to understand the background of women scientist (WS) in studying science, what motivate them to choose science and technology field, exploring their achievement, understanding their social support, exploring their problems. This research was qualitative case study approach. The key informant were four who come from Industrial Engineering and Mathematics and Science Faculty of Universitas Islam Indonesia. The data collection method used depth interviews, observation and documentation. The data test method used triangulation while analysis uses reduction-display-conclusion. The research found that WS studied science because of their interest of internal factor and the environment role of external factor. Their motives also gave benefit for others and increase their networking that is bit similar to McClelland’s Theory. WS had high excellent achievement in functional and structural positions, they received awards from their university until international award which are related to their research result. They also occupied important university structural position. They faced role conflict problem which similar to Greenhaus and Beutell (1985) Theory which increase their behavior changing. They faced marginalization because of their marital status and fear of success tendency which are losing cooking skills and having risk of not having friends which similar to Shaw and Costanzo (1982) Theory.